Post COVID-19 Sequelae in Adults: A Review - Permatasari, Devina Indah (Health Information : Jurnal Penelitian, 2023)
Post-COVID syndrome is a multisystem disorder that develops after an acute illness. Numerous studies of past respiratory virus pandemics have shown persistence of various symptoms, fatigue, shortness of breath, and cognitive dysfunction that are frequently mentioned. The research carried out use a systematic literature search, a systemic search of published was performed in the databases PubMed and ScienceDirect. To find papers search terms “Post COVID-19”, “SARS-Cov-2”, “Sequelae” and “Adult”. The online search performed between December 2022 to April 2023. The results from the 14 journals used in this study consisted of 9 journals with cohort studies, 3 journals cross sectionals, 2 journals systematic reviews. Fatigue was the most common sequelae (71,4%), shortness of breath (64,1%), anxiety/depression (35,7%), memory and attention deficits (21,4%), myalgia/joint pain (21,4%), Smell/taste disorders (21,4%), hair loss (14,2%), and (7,1%) weakness legs, pain when breathing, cough, tiresness, headaches, problems seeing or blurred vision, hyperhidrosis, insomnia, sore throat, rhinitis, diarrhoea, ageusia, impaired pulmonary function, abnormal CT findings including pulmonary fibrosis, incurred greater risk of heart failure. There are many Sequelae in post COVID-19 sufferers, this will affect the target organs in the body. Fatigue is the most reported sequelae.